SOCIO-ECONOMIC AWARENESS ON PROTECTING LAKE MANINJAU USING WILLINGNESS TO PAY - Putri, Intan Adhi Perdana (Jurnal Sosial Ekonomi Pekerjaan Umum, 2017)
Lake Maninjau used for multiple purposes such as Hydropower, aquaculture, fishing, tourism, and irrigation. Lake claimed as common pool resources, a characterized of this resources are everybody's property is nobody's property, so that when there is damage or environmental degradation occurred, then no one is responsible. As is the case in Lake Maninjau. Environmental damage caused by a lot of economic activities such as fish farming with intensive systems, agriculture, and solid waste from household activities. The community around Lake Maninjau consents that the environmental degradation occurred in this lake, approximately 69 percent of respondents consent that the quality of water in the lake is now worse than the last ten years. This paper will show on how the relationship between household willingness to pay (WTP) for Lake Maninjau preservation based on its socio-economic factors. Furthermore, the WTP analyzed using multiple regression. The dependent variable of this paper is the willingness to pay for conservation of the lake Maninjau), while the independent variable is the socio-economic variables namely age, income, education, gender, main occupation, and citizenship status. The result shows that WTP value of each respondent was relatively small, only $ 2.3/hh/year. However, propitiously, young people have a higher WTP values, expected future generation will be more aware of sustainability Lake Maninjau.